Effect of aqueous and alcoholic extract of Eucalyptus camaldulensis Dehn leaves in growth of root rot fungi of Biota orientails L. in vitro - muhannad younis; Anwer Al-khero (College of Education for Pure Sciences, 2022)
Root Rot disease is one of important disease which caused great damage for Biota orientails and this was evident in the private forest nurseries in Mosul, for three nurseries in the Al-Faisaliah area, three nurseries in the Muthanna area, one nursery in the Mohandessin area, as well as the Nineveh horticultural station during the field survey, this was through October and December of 2017 and February - August of 2018.fungi were recorded like Fusarium solani Mart isolation ratia 36.85% ,Macrophomina phaseolina Tassi Goid islalation ratia 22.34% and Rhzoctonia solani Khun islalation ratia 26.89% which Isolated from Biota orientails seedling . Results of pathogenicity tests showed Fusarium solani was had high pathogenicity (50%) Biota orientails seedling and the fungus was very effective at growth characteristics. study of Eucalyptus camaldulnsis leaves Extracts effect at the growth of Isolated fungi The results showed the superiority of the alcoholic extract in inhibiting the growth of the isolates fungi compared to the aqueous extract and for all concentrations except for the fungus R. solani, which was uniquely significantly inhibited by the effect of the aqueous leaf extract of Eucalyptus.